Team-building exercises. Planning activities that actually work - Oprya, Natalia (My University, 2014)
Too often, managers plan their activity with no real thought or goal in mind. This tends to be a waste of time, and managers risk to lose the team's respect when they plan an exercise that doesn't actually help those involved.Team-building exercises can be a powerful way to unite a group, develop strengths, and address weaknesses - but only if the exercises are planned and carried out strategically. In other words, there has to be a real purpose behind your decision to do the exercise, for example, improving the team's problem-solving or creativity skills rather than because you felt like giving your people a nice day out of the office.
Keywords: planning; managers; team-building; планирование; менеджеры; тимбилдинг; планування; менеджери; тімбілдінг